Mucinous cystadenoma with ossification: An uncommon finding in a common neoplasm (Indian Journal of Case Reports, 2025)
Lamellar bone formation (osseous metaplasia/heterotopic bone formation) is an unusual occurrence in the ovary, with the exception of mature cystic teratoma. Herein, we report a case of incidental finding of heterotopic bone formation in a mucinous cystadenoma of the ovary in a 59-year-old female who presented with abdominal pain. The subsequent evaluation led to the detection of the right hydrosalpinx, for which she underwent total abdominal hysterectomy with bilateral salpingo-oophorectomy. Gross examination of the specimen received showed an enlarged cystic right ovary and atrophic uterus. The microscopic examination revealed a right ovarian mucinous cystadenoma with foci of ossification. Ossification in an ovarian cyst is a benign finding of minimal prognostic significance. However, awareness of this entity is necessary to understand the sonographic findings of apprehension during radiological examination.